Analisis Deiksis Dalam Film “Mencuri Raden Saleh” Karya Angga Dwimas Sasongko - Ananda Fatimah Azzahro; Nyar Osmi Arianti; Aditya Rahayu; Afina Maharani; Elisa Natika Hutabarat; Asep Purwo Yudi Utomo; Yusro Edy Nugroho (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Deixis are various things that relate closely to the grammaticalization of the characteristics of a language context or linguistic events relevant to linguistic interpretation, which is highly dependent on the context itself. Dialogues in movies can bring up various deixis, such as in